2014
DOI: 10.1080/15374416.2014.940623
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and the Family Check-Up: Changes in Observed Parent-Child Interaction Following Early Childhood Intervention

Abstract: Coercion theory posits a cyclical relationship between harsh and coercive parent–child interactions and problem behavior beginning in early childhood. As coercive interactions have been theorized and found to facilitate the development and growth of early conduct problems, early interventions often target parenting to prevent or reduce early disruptive problem behavior. This study utilizes direct observations of parent–child interactions from the Early Steps Multisite study (N = 731; 369 boys) to examine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 70 publications
7
48
0
4
Order By: Relevance
“…Perhaps increasing observation times even further, particularly under conditions of some stress and a salient, emotionally charged conflict between the mother and the child, would allow for a more robust measurement of power assertion. We note, however, that the findings were nevertheless consistent with our expectations, with our past work with community samples, and with extant research that involved mothers and toddlers at a higher risk (e.g., Sitnick et al, 2014). …”
Section: Discussionsupporting
confidence: 89%
“…Perhaps increasing observation times even further, particularly under conditions of some stress and a salient, emotionally charged conflict between the mother and the child, would allow for a more robust measurement of power assertion. We note, however, that the findings were nevertheless consistent with our expectations, with our past work with community samples, and with extant research that involved mothers and toddlers at a higher risk (e.g., Sitnick et al, 2014). …”
Section: Discussionsupporting
confidence: 89%
“…A lack of intervention effects on the coercion trajectory and no moderation by intervention group increases our confidence that the findings represent a naturally occurring relationship between RSs and coercion dynamics. Two other studies from this dataset have also reported nonsignificant direct effects of the FCU on coercive processes in early childhood (Sitnick et al, in press; Smith et al, in press). Sitnick and colleagues found an effect of the intervention on increases in positive interactions from age 2 to 5, which was associated with declines in observed coercion over time.…”
Section: Discussionmentioning
confidence: 50%
“…In an intensive analysis of observed family interaction as a mediator of long-term outcomes, Sitnick et al (2014) found that long-term reductions in children’s aggressive and oppositional behavior was mediated by yearly improvements in parents’ observed positive behavior support as well as coercive conflict. Finally, Shaw also found moderate effects on reductions in maternal depression in early childhood, in both studies (Shaw et al, 2006; Shaw, Connell, Dishion, Wilson, & Gardner, 2009).…”
Section: A Model-based Family Intervention Modelmentioning
confidence: 99%